Nurturing transformative adaptation to climate change: A methodology guide centered on social equity - Petesch, Patti; Fisher, Eleanor; Ebenstal Almeida, Olivia; Hellin, Jon; Bullock, Renee (International Rice Research Institute, 2024)
This guide is a principal output of a qualitative methodology study that explored people’s understandings of and experiences with social equity and adaptation to climate change in smallholder agricultural communities. Study objectives featured development and testing of research methods that worked to reveal openings for positive change and potentially disrupt drivers of vulnerability and resource scarcity. The learning approach addresses an urgent need for greater understanding of social processes that advance equitable adaptation. The methodology was tested with 323 study participants in six villages of Kenya and the Philippines in 2023 and 2024. The guide is shared in the spirit of nurturing further “bottom-up” action learning on social equity and climate adaptation. This publication provides an interim version while a fuller methodology guide is in process.